Surveys of the populations of Phytoseiid mites in the vineyard and on natural vegetation (Bollettino di zoologia agraria e bachicoltura, 2024)
The results of a work whose aim is to highlight the existing interactions between the vineyard and natural vegetation with refer~nce to the populations of Phytoseiid mites have been reported. The research was carried out in Lombardy in the viticultural area of Franciacorta, during 1997 and 1998 and in 2001. Samples were taken from the foliage of the cultivation and on the most abundant natural species and the passive aerial dispersal of the Phytoseiid mites was evaluated. The importance of trees in sustaining great populations of these predators was confirmed, among which there was Kampimodromus aberrans (Oud.) that dominates on the vine. The Phytoseiid mites were only sporadically found on grass except on Urtica dioica where two species were found; Phytoseius gr. horridus and, to a lesser extent, K. aberrans. The movement within the agro-ecosystem via air currents of the Phytoseiid mites present on tree vegetationwas ascertained. The evolution of the colonisation of the vineyards was faster in the plots surrounded by wooded areas. The populations reached a very high density and were dominated by K. aberrans. Where there was only grass the populations of Phytoseiid mites remained low and was made up of vicarious species, such as Amblyseius andersoni (Chant) and Typhlodromus pyri Scheuten.